ICT Usage and Implementation of Competence-Based Curriculum in Selected Secondary Schools in Kabale Municipality. - Mugabe, Samuel (Kabale University, 2023)
This study was carried out on ICT Usage and Implementation of Competence-Based Curriculum in Selected Secondary Schools in Kabale Municipality. The study adopted a cross-sectional, correlational survey design where data was collected from selected secondary schools and analyzed at once. The population of the study included teachers and directors of studies. The study included a sample of 108 respondents who included 104 respondent teachers and 4 directors of studies (Key Informants). Different data collection instruments and methods were used to collect data respondents in that questionnaires were used to select teachers and interview guide was used to key informants (Director of studies) All the data collected from the respondents were analyzed using Statistical Package for the Social Sciences (SPSS) version 14. The analysis included descriptive analysis using mean and percentages, tables, pie charts, and graphs. Qualitative data was analyzed using thematic analysis where data was arranged into codes and themes. Findings indicate that the Level of ICT use that the level is relatively high. On Teachers’ perception towards ICT integration in the competence-based curriculum, it was strongly agreed that teachers had shown a positive attitude toward ICT integration in the competence based curriculum. On the relationship between teachers’ perception toward ICT integration and ICT infrastructure there was a positive regression. The study recommended that schools need to have adequate and up-to-date ICT infrastructure, including hardware, software, and connectivity; Teachers need to be trained in how to effectively integrate ICT into their teaching practices; Encourage collaboration and sharing of best practices; ICT should be integrated into all subject areas, not just in computer studies or ICT classes; Schools should regularly evaluate the impact of ICT integration on student learning outcomes and Schools need to provide ongoing support to teachers and students to ensure that they are able to use technology effectively. This can include technical support, troubleshooting, and mentoring.